1964
DOI: 10.1139/y64-047
|View full text |Cite
|
Sign up to set email alerts
|

The Action of a Proteolytic Enzyme From Aspergillus Oryzae on Components of the Blood Clotting System

Abstract: @r1.7, a highly purified proteolytic eilzyrne fr-on1 ~l s p e r g i l l~~v orysae, acts 011 a 11nrnbea of the c~:~yulatiori iactors. I n low c-oncentrrstio~~s, inlrncclinte action is to decrease the rec.alcifleti clottirrg tirne. 'The c\idcc~ce, as furrlish~d by exg~erirnientl-011 a prothroinbin fractio~i, is t h a t it C~) C S thi:, tiy co~iv~'rhi~lg pruthronltin to thronr~bii~. In this regard its actio11 is similar to that of thr-onil~r~plastii~. Ilurialg inc-uI,ation, espec*irnl%y mith ialcreasing concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1966
1966
1982
1982

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The results of Monkhouse et al [ 18] are in favor of the first explanation: Addition of brinase to a bovine prothrombin solution caused in an isolated in vitro system acceleration of prothrombin to thrombin, in the presence of calcium. The authors concluded from these findings that brinase converted prothrombin to thrombin.…”
Section: Discussionmentioning
confidence: 92%
“…The results of Monkhouse et al [ 18] are in favor of the first explanation: Addition of brinase to a bovine prothrombin solution caused in an isolated in vitro system acceleration of prothrombin to thrombin, in the presence of calcium. The authors concluded from these findings that brinase converted prothrombin to thrombin.…”
Section: Discussionmentioning
confidence: 92%
“…However, it is a very toxic compound which has profound effects on the coagulation mechanism and the effective doses are so close to the toxic or even fatal dose that it seems almost certain it will not be clinically useful (22).…”
Section: Possibilities Of Development Of Fibrinolytic Activitymentioning
confidence: 99%
“…Insufficient dosage, although being without toxicity, was ineffective in lysing thrombi. (Very low dosage carried the additional hazard of being thrombogenic.3~ 6,11) Owing to this narrow range of therapeutic effectiveness (i.e., the need for attainment of a delicate balance between the lowering of CA-7 inhibitors to the level of fibrinolysis, and their total depletion), a closer examination of the occurrence of systemic toxic sequelae within this range appeared essential. EXPERIMENTAL Thirty-six mongrel dogs between 12 and 20 kg in weight were identically treated with a variety of CA-7 preparations.…”
mentioning
confidence: 99%